Pathophysiology and implications of intradialytic hypertension. Issue 4 (July 2017) - Van Buren, Peter Noel
Abstract : Purpose of review: Intradialytic hypertension occurs regularly in 10–15% of hemodialysis patients. A large observational study recently showed that intradialytic hypertension of any magnitude increased mortality risk comparable to the most severe degrees of intradialytic hypotension. The present review review discusses the most recent evidence underlying the pathophysiology of intradialytic hypertension and implications for its management. Recent findings: Patients with intradialytic hypertension typically have small interdialytic weight gains, but bioimpedance spectroscopy shows these patients have significant chronic extracellular volume excess. Intradialytic hypertension patients have lower albumin and predialysis urea nitrogen levels, which may contribute to small reductions in osmolarity that prevents blood pressure decreases. Intradialytic vascular resistance surges remain implicated as the driving force for blood pressure increases, but mediators other than endothelin-1 may be responsible. Beyond dry weight reduction, the only controlled intervention shown to interrupt the blood pressure increase is lowering dialysate sodium. Summary: Patients with recurrent intradialytic hypertension should be identified as high-risk patients. Dry weight should be re-evaluated, even if patients do not clinically appear volume overloaded. Antihypertensive drugs should be prescribed because of the persistently elevated ambulatory blood pressure. Dialysate sodium reduction should be considered, although the long term effects of this intervention are uncertain.